PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK DAN PROGRAM SAMSAT CORNER TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Lulu Amalia Nusron; Vidya Vitta Adhivinna; Vitya Risti Andari (JURNAL FAIRNESS, 2023)
The aim of this research is to test whether tax compliance is influenced by knowledge, awareness and the Samsat corner program at SAMSAT Sewon Bantul. The population of this research is the taxpayer at SAMSAT Corner Sewon Bantul Yogyakarta with 100 people as the sample and accidental sampling is the technique of taking it. This research is quantitative with a list of questions as a means of collecting data and analyzed by multiple regression. The research results obtained were that tax payment compliance was positively influenced by knowledge, awareness and the SAMSAT Corner program.